2010
DOI: 10.4314/wsa.v36i1.50914
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of five extraction methods for extracellular polymeric substances (EPS) from biofilm by using threedimensional excitation-emission matrix (3DEEM) fluorescence spectroscopy

Abstract: Two physical methods (centrifugation and ultrasonication) and 3 chemical methods (extraction with EDTA, extraction with formaldehyde, and extraction with formaldehyde plus NaOH) for extraction of EPS from alga-bacteria biofilm were assessed. Pretreatment with ultrasound at low intensity doubled the EPS yield without significant modification of the composition of EPS. Extraction with EDTA or extraction with formaldehyde plus NaOH increased yield by about 1 order of magnitude compared with other methods. However… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
54
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(55 citation statements)
references
References 25 publications
0
54
0
1
Order By: Relevance
“…Only methods that can solubilize the gel matrix are capable of extracting structural EPS. In this research, some frequently used EPS extraction methods such as centrifugation [10][11][12][13][14][15] , sonication 10,14,15 , EDTA [10][11][12]14,15 , formaldehyde + NaOH [10][11][12][13][14][15] and formamide + NaOH 13 could not efficiently isolate the structural EPS. This is due to the fact that the hydrogel matrix of the aerobic granules was not solubilized by these methods.…”
Section: Remarks For the Protocol Sectionmentioning
confidence: 99%
“…Only methods that can solubilize the gel matrix are capable of extracting structural EPS. In this research, some frequently used EPS extraction methods such as centrifugation [10][11][12][13][14][15] , sonication 10,14,15 , EDTA [10][11][12]14,15 , formaldehyde + NaOH [10][11][12][13][14][15] and formamide + NaOH 13 could not efficiently isolate the structural EPS. This is due to the fact that the hydrogel matrix of the aerobic granules was not solubilized by these methods.…”
Section: Remarks For the Protocol Sectionmentioning
confidence: 99%
“…Pan et al [26] reported that chemical methods significantly increased the extraction yield from natural biofilm compared to physical methods. Nevertheless, the use of chemical methods can modify the composition of the EPS extracted.…”
Section: Introductionmentioning
confidence: 99%
“…However, if the protein content in an EPS sample is low, it is barely detected by the Bradford method. In such cases, 3D-EEM is a more sensitive method for detecting low contents of protein or protein-like substances (Pan et al 2010). Furthermore, 3D-EEM can be used to distinguish fluorescent compounds that may exist in the complex EPS mixtures (Sheng and Yu 2006); however, because of its insensitivity to polysaccharides, the fluorescence signals of EPS are primarily attributable to proteins or humic substances (Laspidou and Rittmann 2002).…”
Section: Chemical Analysis Methodsmentioning
confidence: 99%
“…Low yield of EPS, little protein (Pan et al 2010), ineffective for bound EPSs (Pal and Paul 2008) Ultrasonication High protein yield (Pan et al 2010) Ineffective degradation of some components of EPS (Pan et al 2010) Chemical methods EDTA High EPS yield (Pal et al 2008;Metzger et al 2009) Low protein and carbohydrate contents; extractant affects EPS composition (Pan et al 2010) CER Mild, effective, low cell mortality rate (Frolund et al 1996;Karunakaran et al 2011), higher protein content (D'Abzac et al 2010) Low nucleic acid contents (D'Abzac et al 2010), difficult to identify the specific EPS fractions involved in metal bindings (Stewart et al 2013).…”
Section: Extraction Methodsmentioning
confidence: 99%